ANALISIS KELAYAKAN BUKU TEKS BINA AQIDAH AKHLAK KELAS 5 SEKOLAH DASAR/MADRASAH IBTIDAIYAH - Cahya Utami, Dewi; Mutia Jamelia, Dhea; Valia Amandla, Khansa; Ayunda Sari, Suci; Hamidah, Siti; Nopasari, Dewi (Sindoro: Cendikia Pendidikan, 2024)
This study aims to analyze the feasibility of the “Bina Aqidah Akhlak” textbook for grade V elementary/madrasah Ibtidaiyah schools. Using the literature study method, this research evaluates four main aspects: content, presentation, language, and graphics according to the provisions of the National Education Standards Agency. The results showed that the book met the eligibility criteria with a total score of 89.7, indicating a “Highly Appropriate” category on the suitability of the material with the basic competencies, accuracy of information, and structured presentation. However, there are some areas that need improvement, especially in simplifying complex concepts and developing learning support materials. This research is expected to provide constructive recommendations for the development of better quality textbooks that are relevant to current educational needs. Keywords: book eligibility, religious education, content analysis, textbooks.